Standard operating procedure for post-operation component disassembly and observation of benchtop water electrolyzer testing - Glenn, Jennifer R.; Lindquist, Grace A.; Roberts, George M.; Boettcher, Shannon W.; Ayers, Katherine E. (Frontiers in Energy Research, 2022)
Post-operation component disassembly and observation of electrolyzer parts is useful in understanding the interactions of the components and the electrochemical environment beyond the systems electrochemical output. We report a standard protocol for post-operation component disassembly and observation, including directions for cell-component preservation, preliminary visual inspection of cell components, and a guide for the advanced inspection of specific components with suggestions for further analysis if necessary. The procedures outlined here allow for a standardized method that can be used and compared between different laboratories and for literature comparison to experimental results.